Efektivitas Kerja Receptionist Dalam Menangani Tamu Check – In Pada Masa Pandemi Covid-19 Di Jumana Bali Ungasan Resort - Anak Agung Istri Sri Anjasuari; Anak Agung Istri Ratna Sari Wulan; Dewa Gede Putra (Journal of Hospitality Accommodation Management (JHAM), 2022)
This final project research takes place at Jumana Bali Ungasan Resort.The purpose of this research is to determine the effectiveness of receptionist work in handling guest check-in during the COVID-19 pandemic at Jumana Bali Ungasan Resort. The data collection and analysis are in the form of documentation and interviews. It was found that several things were not done, including the receptionist who had not arrived 5 minutes before the work shift started. From the results of the research that has been described, it is suggested the receptionist is expected to carry out routine training, such as conducting management training for supervisors and all staff related to grooming at work and implementation of health protocols during the pandemic.